Digital Extension Strategies for Empowering Rice Farmers in West Bangka Regency Admid The Agricultural of Era 4.0 Transformation - Yulia; Robika; Fika Dewi Pratiwi (Postgraduate, University of Mataram, 2026)
Agricultural extension plays a strategic role in empowering farmers through non-formal education, particularly in the era of the Agricultural 4.0 transformation, characterized by rapid developments in information technology and digital innovation. This study aims to analyze digital extension strategies in empowering rice farmers in West Bangka Regency, especially in Tebing Village, Kelapa Sub-district. The research employed a qualitative descriptive method using questionnaires distributed to 30 rice farmers selected purposively. The study focuses on farmer characteristics and the role of agricultural extension workers in strengthening farmer empowerment through digital-based communication and information systems. The findings reveal that the characteristics of farmers, including age, formal education, non-formal education, farming experience, and land ownership status, are generally categorized as moderate (40%) in influencing empowerment levels. Meanwhile, the role of extension workers was considered highly significant (80%) in supporting farmer empowerment. In the context of the digital era, extension workers increasingly function not only as facilitators and motivators but also as digital mediators who introduce farmers to information technology, online agricultural marketing, weather and price information systems, and social media-based communication platforms. The integration of digital tools enables farmers to access agricultural knowledge more efficiently, improve decision-making processes, and strengthen market connectivity. This study concludes that digital extension strategies are essential in enhancing the capacity and independence of rice farmers amid the Agricultural 4.0 transformation. The utilization of information technology and digital communication can strengthen agricultural productivity, expand farmers’ access to information, and support sustainable rural agricultural development in West Bangka Regency.